Numerical parameters for deep drawing simulation of a double bowl sink - Sener, Bora; Yurci, Mehmet Emin (CARL HANSER VERLAG, 2017)
Numerical parameters have significant impact on the results of finite element simulations. Wrong selection of these parameters causes erroneous results and too long computation time in the analyses. Therefore, numerical parameters should be selected properly in order to obtain accurate results in the finite element simulations. In this study, the effects of the numerical parameters used in finite element simulations are investigated. Deep drawing of a double bowl sink is modeled and simulations are done with different parameters. Influences of element size and refinement level on the blank, the effect of the number of elements on the die radius and dynamic effects are investigated and optimum parameters are determined. The results obtained are compared with experimental data, and a good agreement is observed.
Keywords: Numerical parameters; finite element simulation; deep drawing; double bowl sink; METAL FORMING PROCESSES; FINITE-ELEMENT; Materials Science